In Pursuit of Honors: A Multi-Institutional Study of Students' Perceptions of Clerkship Evaluation and Grading. (November 2019) - Bullock, Justin L.; Lai, Cindy J.; Lockspeiser, Tai; O'Sullivan, Patricia S.; Aronowitz, Paul; Dellmore, Deborah; Fung, Cha-Chi; Knight, Christopher; Hauer, Karen E.
Abstract : Purpose: To examine medical students' perceptions of the fairness and accuracy of core clerkship assessment, the clerkship learning environment, and contributors to students' achievement. Method: Fourth-year medical students at 6 institutions completed a survey in 2018 assessing perceptions of the fairness and accuracy of clerkship evaluation and grading, the learning environment including clerkship goal structures (mastery- or performance-oriented), racial/ethnic stereotype threat, and student performance (honors earned). Factor analysis of 5-point Likert items (1 = strongly disagree, 5 = strongly agree) provided scale scores of perceptions. Using multivariable regression, investigators examined predictors of honors earned. Qualitative content analysis of responses to an open-ended question yielded students' recommendations to improve clerkship grading. Results: Overall response rate was 71.1% (666/937). Students believed that being liked and particular supervisors most influenced final grades. Only 44.4% agreed that grading was fair. Students felt the clerkship learning environment promoted both mastery and performance avoidance behaviors (88.0% and 85.6%, respectively). Students from backgrounds underrepresented in medicine were more likely to experience stereotype threat vulnerability (55.7% vs 10.9%, P < .0005). Honors earned was positively associated with perceived accuracy of grading and interest in competitive specialties while negatively associated with stereotype threat. Students recommended strategies to improve clerkship grading: eliminating honors, training evaluators, and rewarding improvement on clerkships. Conclusions: Participants had concerns around the fairness and accuracy of clerkship evaluation and grading and potential bias. Students expressed a need to redefine the culture of assessment on core clerkships to create more favorable learning environments for all students. Abstract : Supplemental Digital Content is available in the text.